POTENTIAL FOR THE DEVELOPMENT OF THE SRIWIJAYA KINGDOM PURBAKALA PARK, PALEMBANG CITY, SOUTH SUMATRA PROVINCE - Rosianty, Yuli; Lensari, Delfy; Ardiansyah, Ferdi (Universitas Muhammadiyah Palembang, 2022)
This research was conducted to determine and analyze biodiversity and ecotourism potential in the Archaeological Park of the Sriwijaya Kingdom by gathering information from vegetation analysis of green open spaces (RTH) and conducting interviews and questionnaires to managers and visitors. The method used in this study is descriptive qualitative with data collection techniques of observation, interviews, documentation and literature. The informants in this study were visitors and managers of the Sriwijaya Kingdom Archaeological Park. The results showed that the Archaeological Park of the Sriwijaya Kingdom has the concept of historical and cultural tourism of the Sriwijaya Kingdom with various tourist attractions, namely natural scenery, the beauty of Cempaka and Nangka Islands, biodiversity and historical and cultural heritage of the Sriwijaya Kingdom. Angsana (Pterocarpus indicus) is dominated by Angsana in the ancient park of the Kingdom of Sriwijaya at the pole level with a diameter of 15.36 cm and an IVI value of 75.44. At the tree level, it is dominated by the Banyan (Ficus benjamina) with a diameter of 30.07 cm and an IVI value of 39.61. The condition of the vegetation in the Archaeological Park of the Sriwijaya Kingdom, at the tree level, there are many old trees with dense crowns with a diameter of ± 30 cm and stems and branches that are starting to die, such as Banyan trees and Angsana, to overcome the problems that arise. there is replanting and adding trees that have ecological and educational functions. The potential for developing urban parks in the Archaeological Park of the Sriwijaya Kingdom has four potentials, namely ecological potential, social potential, cultural and historical potential and economic potential. Based on the SWOT analysis, the potential for developing urban parks in the Archaeological Park of the Sriwijaya Kingdom is maintaining the potential of urban parks, improving services, professional human resources, facilities and infrastructure and developing ecotourism products by utilizing urban and historical parks and maintaining existing tourism concepts. The strengths of the Sriwijaya Kingdom Archaeological Park are tourism that is favored by teenagers and students, the existence of facilities and infrastructure, accessibility, attractive and diverse tourism potential, having the beauty of the city and cultural history and having biodiversity. The weaknesses of the Sriwijaya Kingdom Archaeological Park are the lack of promotion on social media, the condition of damaged infrastructure and incomplete infrastructure, not having sufficient budget for even better development, limited human resources and lack of area security due to the extent of the Royal Archaeological Park Srivijaya.